Low back pain prevention behaviors and beliefs among the Polish population in a cross-sectional survey - Kuśmierek, Paulina; Mikołajczyk, Mateusz; Złotkowska, Dagmara; Łowczak, Anna; Mikołajczyk, Anita (Frontiers in Public Health, 2024)
Background: Low back pain (LBP) is one of the most common problems of public health and creates a burden globally. The aim was to assess the Polish population's back pain prevention behaviors and beliefs and to examine how these health behaviors and beliefs vary across sociodemographic factors and physical activity.A cross-sectional survey was carried out among 208 randomly selected patients of the public general practitioner clinic. The differences in LBP-related beliefs and attitudes were determined due to participants' status of requiring or non-requiring LBP treatment.Results: More than half of the respondents did not engage in behaviors that protect against back pain. Individuals with higher education levels and those who exercised at least once a week were significantly more likely to adopt behaviors to protect their backs. Less than half of the participants reported having a workplace that was adequately prepared to protect against back pain, and only 35.1% of the participants reported receiving instruction while taking up work on how to avoid back pain while working. According to respondents' opinions, preventive actions are necessary to protect against back pain. Inappropriate exercises and stress can be contributors to back pain, with these opinions reported more often by women and participants with higher education levels. Participants who received treatment for LBP showed a significantly higher expression of behaviors to protect against back pain compared to participants who did not require treatment. However, there were no significant differences in participants' beliefs about back pain prevention between the group requiring LBP treatment and the group not requiring LBP treatment.The study provides valuable insights into the association between LBP treatment, back pain prevention behaviors, and beliefs, suggesting potential avenues for future research and intervention development. By addressing workplace ergonomics and promoting a culture of back health, it may be possible to reduce the burden of LBP in Poland.